Is there a normal magnetic-polarity event during the Palaeocene–Eocene thermal maximum (∼55 Ma)? Insights from the palaeomagnetic record of the Belluno Basin (Italy) - E. Dallanave; C. Agnini; L. Tauxe; D. Rio; G. Muttoni (Geophysical Journal International, 2012)
In the lowermost Eocene sedimentary record of Ocean Drilling Program Site 1262 (Leg 208, Walvis Ridge, South Atlantic Ocean), the presence of a similar to 53-kyr-long normal polarity event has been recorded within the similar to 2.55-Myr-long reverse polarity Chron C24r (similar to 53.355.9 Ma) and termed PalaeoceneEocene magnetic reversal (PEMR). The origin of the PEMR has been speculatively related to a change in the Earth's rotation rate that was in turn influenced by an abrupt overturning of the ocean-atmosphere circulation that occurred during the PalaeoceneEocene thermal maximum (PETM) at similar to 55 Ma. Such provocative genesis for a magnetic-polarity reversal demands the PEMR to be confirmed (or refuted) in additional PETM sections. Here, we present detailed palaeomagnetic and rock-magnetic data from the Forada and Cicogna sections of the Belluno Basin in NE Italy, which contain an expanded and continuous record of the PETM termed clay marl unit (CMU). Our data indicate that these sediments were deposited during a continuous interval of reverse geomagnetic field polarity. We therefore conclude that no magnetic-polarity reversals occurred throughout the PETM. In addition, we studied the origin of the high degree of flattening affecting the characteristic magnetic component directions of the sediments, which we interpret as due to a combination of depositional inclination shallowing typical of detrital haematite, and post-depositional compaction of clays, particularly abundant in the carbonate-depleted CMU.